Trust and Fairness in Open, Distributed Systems - Wierzbicki, Adam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is an attempt to bring closer the greater vision of the development of Social Informatics. Social Informatics can be defined as a discipline of informatics that studies how information systems can realize social goals, use social concepts, or become sources of information about social phenomena. All of these research directions are present in this book: fairness is a social goal; trust is a social concept; and much of this book bases on the study of traces of Internet auctions (used also to drive social simulations) that are a rich source of information about social phenomena. The book has been written for an audience of graduate students working in the area of informatics and the social sciences, in an attempt to bridge the gap between the two disciplines.
Theory of Trust and Fairness -- Trust Management -- Fairness Management -- Conclusion.
Keywords: Engineering; Computer Communication Networks; Artificial intelligence; Social sciences -- Data processing; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Computer Appl. in Social and Behavioral Sciences; Computer Communication Networks